Diary of a Wimpy Kid : Old school - Kinney, Jeff (UK Puffin Books, 2017)
Life was better in the old days. Or was it? That's the question Greg Heffley is asking as his town voluntarily unplugs and goes electronics-free. But modern life has its conveniences, and Greg isn't cut out for an old-fashioned world. With tension building inside and outside the Heffley home, will Greg find a way to survive? Or is going 'old school' just too hard for a kid like Greg?
Include Illustration
Keywords: Heffley, Greg -- Juvenile fiction